Microwave-induced plasma reduction of Sc2O3 for sustainable Al3Sc alloy production: In Situ analysis of Al3Sc formation mechanisms - Fukushima, Jun; Okawa, Yuya; Miyazawa, Tomoaki; Takizawa, Hirotsugu; Fujii, Satoshi (Frontiers in Chemistry, 2025)
This study aimed to elucidate the reaction mechanism of the microwave irradiation method, a novel approach for synthesizing scandium (Sc) and aluminum (Al). Sc2O3 and Al mixed powders were exposed to Mg vapor or Mg plasma. In situ gas analysis and XRD analysis revealed that Al3Sc was formed as a result of Al pulling out Sc while Mg acted as an oxygen getter. In particular, Mg plasma was shown to directly reduce Sc2O3 and significantly increase Al3Sc formation due to its high-energy state. These findings highlight the crucial role of Al and Mg vapors in the synthesis of Sc-containing alloys and demonstrate that Mg plasma accelerates the reaction rate through a distinct mechanism compared to Mg vapor. This study’s outcomes are expected to contribute to the development of environmentally friendly and efficient processes for producing Sc-containing aluminum alloys using Sc2O3, a material challenging to smelt by conventional methods.